1994
DOI: 10.1139/z94-027
|View full text |Cite
|
Sign up to set email alerts
|

Climate, trophic factors, and breeding patterns of the Nile grass rat (Arvicanthis niloticus solatus): a 5-year study in the Sahelian region of Burkina Faso (formerly Upper Volta)

Abstract: 1994. Climate, trophic factors, and breeding patterns of the Nile grass rat (Arvicanthis niloticus solatus): a 5-year study in the Sahelian region of Burkina Faso (formerly Upper Volta). Can. J. Zool. 72: 20 1 -2 14. From 1984 to 1989, five populations of the Nile grass rat, Arvicanthis niloticus solatus, living in five different habitats of the Sahelian region were studied in northern Burkina Faso (Oursi, 14"N). The following were investigated: (i) seasonal variations in the percentages of sexually active mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…In both cases, after 50 days of exposure to these conditions, a slight stimulation of sexual activity was observed in initially sexually inactive animals; and although the treatment resulted in decreased TW (900-1400 mg/100 g BW) and T in animals that were sexually active at the beginning of the experiment, the values nevertheless provide evidence that testicular activity was maintained and allowed the animals to continue breeding. Field observations [7] showed that the presence in a given environment of A. niloticus males with a TW of 900 mg/ 100 g BW is a good indication that the population is breeding, since pregnant females and juveniles were captured at the same time. Nevertheless it should be stressed that the gonadal stimulation observed in animals maintained in either humid conditions or low temperatures occurred only under the short photoperiod.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In both cases, after 50 days of exposure to these conditions, a slight stimulation of sexual activity was observed in initially sexually inactive animals; and although the treatment resulted in decreased TW (900-1400 mg/100 g BW) and T in animals that were sexually active at the beginning of the experiment, the values nevertheless provide evidence that testicular activity was maintained and allowed the animals to continue breeding. Field observations [7] showed that the presence in a given environment of A. niloticus males with a TW of 900 mg/ 100 g BW is a good indication that the population is breeding, since pregnant females and juveniles were captured at the same time. Nevertheless it should be stressed that the gonadal stimulation observed in animals maintained in either humid conditions or low temperatures occurred only under the short photoperiod.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, testicular regression occurs when day length reaches more than 11 h 30 min in Burkina Faso and more than 12 h 15 min in Mali. In Burkina Faso, testicular activity remains intense throughout the cold dry season (beginning of December to the end of January) and continues at the same level during the first part of the hot dry season, due to the advantageous feeding habits of this species (consumption of insects and of the bark of Acacia seyal, which has a high water content) [7,16]. Testicular activity subsequently regresses due to the combined effects of the long photoperiod, high temperatures, and drought.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations